Why training older employees is less effective - Thomas Zwick (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
This paper shows that training of older employees is less effective. Training effectiveness is measured with respect to key dimensions such as career development, earnings, adoption of new skills, flexibility or job security. Older employees also pursue less ambitious goals with their training participation. An important reason for these differences during the life cycle might be that firms do not offer the 'right' training forms and contents. Older employees get higher returns from informal and directly relevant training and from training contents that can be mainly tackled by crystallised abilities. Training incidence in the more effective training forms is however not higher for older employees. Given that other decisive variables on effectiveness such as training duration, financing and initiative are not sensitive to age, the wrong allocation of training contents and training forms therefore is critical for the lower effectiveness of training.
Keywords: J10; J24; J28; 330; Training; Older Employees; Linked-Employer-Employee Data; Ältere Arbeitskräfte; Weiterbildung; Wirtschaftlichkeit; Deutschland